Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/14673584221100719
|View full text |Cite
|
Sign up to set email alerts
|

Community-based tourism in East Asia: A bibliometric research note

Abstract: Community-based tourism (CBT) is part of East Asia’s tourism landscape as local communities seek to diversify their livelihoods towards tourism. However, little is known about the evolution of research surrounding CBT in the region. Through undertaking a bibliometric analysis of 401 Scopus-indexed articles, this research found that CBT practices have increasingly questioned the legitimacy and authenticity of its value to local communities. Findings also illustrated most studies centred on China, and co-authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The study revealed that community tourism practices question the legitimacy and authenticity of its value to local communities, which may be motivated by the lack of a theory that provides knowledge in this regard. The work proposes the need to carry out theoretical studies based on the assessment of practice, which generate knowledge and allow progress in the research and application of community tourism in East Asia [158].…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that community tourism practices question the legitimacy and authenticity of its value to local communities, which may be motivated by the lack of a theory that provides knowledge in this regard. The work proposes the need to carry out theoretical studies based on the assessment of practice, which generate knowledge and allow progress in the research and application of community tourism in East Asia [158].…”
Section: Discussionmentioning
confidence: 99%